A STAT factor mediates the sexually dimorphic regulation of hepatic cytochrome P450 3A10/lithocholic acid 6 beta-hydroxylase gene expression by growth hormone. - Subramanian, A (1995)
Adult male rodents have a pulsatile profile of growth hormone (GH) release, whereas female rodents have a relatively steady-state pattern with uniform, albeit lower levels of GH. The expression of a number of sexually differentiated hepatic proteins is primarily determined by these plasma GH profiles and only secondarily regulated by gonadal hormones. An important subset of these sexually dimorphic proteins is cytochrome P450s. CYP3A10/6 beta-hydroxylase is a cytochrome P450 that catalyzes the 6 beta-hydroxylation of lithocholic acid. CYP3A10/6 beta-hydroxylase is expressed only in male hamsters; however, mimicking the male GH secretion pattern in females induces expression of the gene to male levels. Using chimeric CYP3A10/6 beta-hydroxylase promoter/luciferase reporter genes transfected into hamster primary hepatocytes, we have shown a GH-mediated induction of promoter activity. A combination of 5'-deletion constructs, heterologous promoter constructs, and specific mutagenesis was used to localize the DNA element involved in the GH-mediated regulation of CYP3A10/6 beta-hydroxylase promoter activity, which resembles a STAT binding site. Footprint and gel shift analyses confirmed that the expression of the protein binding to this site is regulated by GH and that the DNA-protein complex can be partially supershifted by anti-STAT-5 antibodies. This protein is 50% more abundant in male than in female hamster livers, is absent in hypophysectomized female livers, and is restored when hypophysectomized females are injected with GH in a manner that masculinizes female hamsters in terms of CYP3A10/6 beta-hydroxylase expression. The system characterized and described here is ideally suited for dissecting the molecular details governing the sexually dimorphic expression of liver-specific genes.